A non-small cell lung cancer fragile elderly patient treated with immunotherapy and non-ablative radiation therapy: a case report of a winning combination - Saddi, Jessica; Santos Hernandez, David Alberto; Stella, Giulia Maria; Galli, Giulia; Borgetto, Sabrina; Bonzano, Elisabetta; Lancia, Andrea; La Mattina, Salvatore; Colombo, Sara; Squillace, Luigi; Baietto, Guido; Bortolotto, Chandra; et al. (Frontiers in Oncology, 2025)
BackgroundRadiation therapy is used in the clinical scenario of oligo-metastatic lung cancer as a weapon to delay the subsequent line of systemic therapy, particularly in the case of oligo-progressive disease. In this setting, the integration of immunotherapy and radiotherapy plays an important role to achieve local control and improve progression-free survival (PFS).Case presentationWe reported the case of an elderly fragile patient affected by advanced non-small cell lung cancer treated with pembrolizumab as first systemic line and immuno-modulant radiation therapy at oligo-progression. More specifically, he underwent stereotactic body radiation therapy using non-ablative regimen (24 Gy in 3 fractions) achieving partial response with abscopal effect and without drug interruption. After one year, during immunotherapy mediastinal and parenchymal progression occurred and he received another radiation treatment using conventional non-ablative regimen (40 Gy in 20 fractions). Complete response was observed without severe side effects (his poor respiratory function did not change during both treatments).ConclusionIn this case report we showed that the association of immunotherapy and non-ablative radiation regimens may represent a safe and effective strategy to achieve complete response also in fragile patients, in whom the burden of side effects should be prioritized.